DOORSMEER BUSINESS RESPONSIBILITY FOR CUSTOMER LOSSES DUE TO WORKER NEGLIGENCE WAHBAH AZ ZUHAILI PERSPECTIVE (CASE STUDY: DOORSMEER PARAMAN MANDIRI, MEDAN AMPLAS) - Weldi Saputra; Rahmat Hidayat (Journal Analytica Islamica, 2025)
Doorsmeer businesses have significant responsibilities and risks in providing vehicle washing services. These risks include negligence that causes losses to customers, such as cars falling due to a broken hydraulic support iron, accidentally pressing the gas pedal before turning off the engine, and cars colliding due to employees' carelessness. It is important to know what form of responsibility is given by the business owner for these losses. This study aims to determine the form of responsibility given by the business owner at doorsmeer Paraman Mandiri, Medan Amplas for customer losses from the perspective of Wahbah Az-Zuhaili. The type of research used is empirical juridical, namely research that examines the direct application of law to an event that occurs in society with qualitative research methods and data collection techniques through interviews and direct observation at doorsmeer. The results of this study indicate that the practice of compensation liability at doorsmeer Paraman Mandiri, Medan Amplas has reflected the principle of justice according to Wahbah Az-Zuhaili's view that liability for damage can be in the form of repairing damaged objects to be whole again. The repair can be done by replacing the same item or by returning the money as done by the owner of the Paraman Mandiri doormeer, namely repairing the damaged car part so that it is intact as before.